The Correlation between Gender and Work Stress with the Fatigue of Lecturers - Kenia Bella Christy; Noeroel Widajati; Yessy Dessy Arna (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Lecturers are workers who are actively involved in educational, research and community service activities at a college. Many duties and responsibilities of lecturers in their work can cause fatigue which is the body's response as a defense mechanism when the work exceeds its capacity. Different capacities can be assessed based on gender which also allows differences in response to the problem. The inability to cope with a problem or job produces a feeling of depression which can also be called as stress. The purpose of this study was to analyze the correlation between gender and work stress with fatigue at a faculty lecturers at a university in Surabaya. Method: This research was an analytical descriptive study in a faculty lecturers at a university in Surabaya. The study design was cross-sectional. Data were obtained through the results of a questionnaire distributed to lecturers who have met the criteria, as many as 43 respondents. Results: The study showed that 16 female respondents (57.2%) experienced moderate fatigue. About 19 respondents (63.3%) had mild stress and experienced mild fatigue. The correlation value between gender and fatigue was 0.816 and the strong correlation between work stress and fatigue was 0.000. This value indicated that there was no correlation between gender and fatigue, but there was a strong and direct correlation between work stress and fatigue. Conclusion: The occurrence of fatigue is not influenced by gender and high fatigue can be influenced by the high work stress felt by them.Keywords:fatigue, gender, lecturer, work stress